English Education Master Students’ Perceptions on Developing Critical Thinking Skills in Academic Writing - Kristian Wijaya (SAGA: Journal of English Language Teaching and Applied Linguistics, 2022)
One of the essential factors strongly supported university EFL learners’ academic writing skills development is critical thinking. With the supports of critical thinking skills, university EFL learners will be capable of synthesizing, analyze, and evaluate their ideas to be written effectively in their academic writing products. This present small-scale qualitative study was conducted with the support of qualitative content analysis to obtain clearer data based on the specific phenomenon told by the research participants. 10 items of the Likert-scale questionnaire as well as 5 open-ended written narrative inquiry questions were administered to 16 English Education Master Students batch 2019, Sanata Dharma University, Yogyakarta. Based on the obtained research results, the utilization of critical thinking skills progressively enabled graduate university EFL learners to be more strategic, analytical, and proficient academic writers. In addition, the participants also acknowledged that critical thinking skills should be practiced intensively in a long-lengthy process to foster their academic writing skills as well. It is expectantly hoped that these obtained results will shed more enlightenment on the further utilization of critical thinking skills for the betterment of academic writing learning activities in the future. Keywords: Critical Thinking Skills, Academic Writing, English Education Master Students